Synthesis of helical branched carbodiimide polymers with liquid crystalline properties. Issue 1 (2nd January 2022) - De Silva, Enosha Harshani; Novak, Bruce M.
ABSTRACT: Carbodiimide polymers are synthetic helical polymers that display unique properties depending on the functional groups attached to the polymer backbone. The amidine groups of the backbone present alternating amine- and imine-like groups. The properties of the polycarbodiimides have been studied by varying the sidechains of the polymer from linear to branched. In previous work, different arenes and straight aliphatic chains substituted polycarbodiimides have been used to evaluate the thermal and liquid crystalline properties of these polymers. In this study, we introduced bulky branched aliphatic and octadecyl side chains to the polymer backbone to generate a branched homopolymer and different branched/linear-chain copolymers. The effect of these side-chain combinations on the solid and solution properties of these polycarbodiimides was studied. It was observed that polycarbodiimides containing octadecyl and branched bulky alkyl groups showed different thermal events in the DSC plot at ~30°C. Also, we observed a decrease in thermal stability in the TGA thermogram as we increase the branched alkyl side chains of the polymers. The lyotropic liquid crystallinity was observed in all the branched copolymers that consist of both branched alkyl side chains and octadecyl functional groups in different ratios. Graphical abstract: uf0001